Uniform lithium deposition guided by Au nanoparticles in vertical-graphene/carbon-cloth skeleton for dendrite-free and stable lithium metal anode. (May 2023) - Xu, Tingting; Hou, Lijuan; Yan, Congcong; Hou, Jingrui; Tian, Bofang; Yuan, Huiyu; Kong, Dezhi; Wang, Hui; Li, Xinjian; Wang, Ye; Zhang, Guopeng
Abstract: Owing to the high electrochemical reactivity and infinite volume expansion of lithium metal anode, the uncontrollable lithium dendrite growth drags the lithium metal anode out of the real application for a long time. Herein, a heterogeneous seed layer of Au nanoparticles (NPs) is uniformly deposited on the 3D porous vertical graphene nanosheets on carbon cloth (Au-VG/CC) to construct a lithiophilic surface, achieving a smooth and dendrite-free morphology. As a result, Au-VG/CC electrode delivers a small voltage hysteresis of 67.2 mV and a long cycling life of more than 500 h at a high current density of 5 mA cm −2 with 5 mAh cm −2 . Results of XRD and in-situ transmission electron microscopy indicate that the formed lithiophilic layer is Li3 Au which can guide the lithium deposition. Moreover, a full battery assembled with Li@Au-VG/CC as the anode and LiFePO4 as the cathode delivers 77.3 mAh g −1 at 100 mA g −1 after 200 cycles. Graphical abstract: Porous 3D Au-VG/CC nanostructure was designed and further adopted as the stable host of lithium metal anodes. Confirmed by the in-situ TEM characterization, the lithiophilicity is originated from the formed Li3 Au alloy which can guide Li deposition with reduced nucleation overpotential, enabling a dendrite free deposition morphology and long cycle stability. Image, graphical abstract